First things first: Internet Relay Chat openings - Rintel, Sean; Mulholland, Joan; Pittam, Jeffrey (Journal of Computer-Mediated Communication, 2001)
Internet Relay Chat (IRC) was the Internet's first widely popular quasi-synchronous computer-mediated communication (CMC) system. While research has consistently demonstrated the interpersonal nature of IRC, and is now turning to more structurally-oriented topics, it is argued that IRC research now needs to systematically address links between interaction structures, technological mediation and the instantiation and development of interpersonal relationships within a framework that privileges IRC interaction and social explanations. This exploration of the openings of IRC interactions is positioned as a step in that direction. The openings investigated in the study are those that occur directly following user's entries into public IRC channels, termed the newly-joined users' Channel Entry Phase (CEP). It is found that turn coordination in the CEP is often ambiguous, has the potential to disrupt relationship development, and leads to considerable emphasis on interactive strategies for the clear ordering of opening phases.
Rintel, E.S., Mulholland, J., & Pittam, J. 2001. First things first: Internet Relay Chat openings. Journal of Computer-Mediated Communication, 6, (3). Online version is free and best version (Use Publisher URL)